EXISTENCE THEOREMS FOR GENERALIZED NASH EQUILIBRIUM PROBLEMS - Dutang, C. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
The generalized Nash equilibrium, where the feasible sets of the players depend on other players’ action, becomes increasingly popular among academics and practitioners. In this paper, we provide a thorough study of theorems guaranteeing existence of generalized Nash equilibria and analyze the assumptions on practical parametric feasible sets.